SPIRITUAL HEALING - A COMPETING OR CO-EXISTING SYSTEM TO ALLOPATHIC MEDICINE - Khan, Noor Ullah; Asif, Nida; Babar, Abdul Manan; Ullah, Hammad (Journal of Postgraduate Medical Institute, 2024)
Objective: To explore the concept of spiritual healing and compare its effects with allopathic medicine in terms of disease conceptualization, treatment approach and patient perception and use in community setting. Methodology: A qualitative research design with a grounded theory approach was utilized for this study. Semi-structured interviews and focus group discussions were conducted, and data were analyzed using thematic content analysis technique. Results: The explorative of spiritual healing revealed motivation challenges and treatment frameworks. Healers emphasized skills mastery and adherence to values, employing methods like Ijazas and wazaiif. Patients reported mixed experiences, with some finding benefit while others expressed their doubt. Comparison with allopathic medicine highlighted drawbacks leading to discussion on preference or potential co-existence. Conclusion: In conclusion, spiritual healing offers a unique perspective on healthcare, while challenges exist, including skepticism and the need for integration with allopathic medicine. The field continues to play a pivotal role in addressing social well being.